2021
DOI: 10.3389/fgene.2021.680537
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal GNAS Contributes to the Extra-Large G Protein α-Subunit (XLαs) Expression in a Cell Type-Specific Manner

Abstract: GNAS encodes the stimulatory G protein alpha-subunit (Gsα) and its large variant XLαs. Studies have suggested that XLαs is expressed exclusively paternally. Thus, XLαs deficiency is considered to be responsible for certain findings in patients with paternal GNAS mutations, such as pseudo-pseudohypoparathyroidism, and the phenotypes associated with maternal uniparental disomy of chromosome 20, which comprises GNAS. However, a study of bone marrow stromal cells (BMSC) suggested that XLαs could be biallelically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Note that maternal XLαs transcription is not completely silenced in hESCs (see Supplementary Fig. 1E), which is consistent with previous studies showing maternal allele contribution to XLαs in bone marrow stromal cells (45,46).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Note that maternal XLαs transcription is not completely silenced in hESCs (see Supplementary Fig. 1E), which is consistent with previous studies showing maternal allele contribution to XLαs in bone marrow stromal cells (45,46).…”
Section: Discussionsupporting
confidence: 91%
“…Bisulfite PCR and amplicon sequencing were performed as we previously described ( 45 ). Genomic DNA was bisulfite converted using the EZ DNA Methylation-Gold Kit (ZYMO RESEARCH) following the manufacturer’s protocol, and each target region was amplified by a single-step PCR using KOD One.…”
Section: Methodsmentioning
confidence: 99%
“…39,41 It is now known that mouse-and humanderived BMSCs and adipose-derived stem cells may exhibit biallelic expression of Gsα equally without gene imprinting expression. 8,34 Thus, it is speculated that the key factor underlying the phenotypic differences in HO within offspring with paternal gene defects in GNAS exons 5-13 (ALEX without defect) may also be associated with another imprinted gene, XLαs. XLαs mRNA is expressed in bone marrow stromal cells and MC3T3-E1 preosteoblastic cells, and the expression of XLαs progressively increases during the differentiation of osteoblasts.…”
Section: Deletion or Activating Mutations Of Xlαs May Synergize With ...mentioning
confidence: 99%
“…Coincidentally, Gsα is biallelic in most tissues but maternal in the vast majority of neuroendocrine tissues 8 . Notably, paternal expression of XLαs may not be absolute, as recent studies have demonstrated that XLαs can be biallelic in mouse‐ and human‐derived BMSCs, with paternal expression higher than maternal expression 34 . By Northern blots and RT‐PCR, XXLαs (extralarge XLαs ) mRNA was detected primarily in the mouse brain, cerebellum, and spleen 19 …”
Section: The Imprinting Expression Of Xlαsmentioning
confidence: 99%
See 1 more Smart Citation